Arachidonoyl-Specific Diacylglycerol Kinase ε and the Endoplasmic Reticulum - Nakano, Tomoyuki; Matsui, Hirooki; Tanaka, Toshiaki; Hozumi, Yasukazu; Iseki, Ken; Kawamae, Kaneyuki; Goto, Kaoru (Frontiers in Cell and Developmental Biology, 2016)
The endoplasmic reticulum (ER) comprises an interconnected membrane network, which is made up of lipid bilayer and associated proteins. This organelle plays a central role in the protein synthesis and sorting. In addition, it represents the synthetic machinery of phospholipids, the major constituents of the biological membrane. In this process, phosphatidic acid (PA) serves as a precursor of all phospholipids, suggesting that PA synthetic activity is closely associated with the ER function. One enzyme responsible for PA synthesis is diacylglycerol kinase (DGK) that phosphorylates diacylglycerol (DG) to PA. DGK is composed of a family of enzymes with distinct features assigned to each isozyme in terms of structure, enzymology and subcellular localization. Of DGKs, DGKε uniquely exhibits substrate specificity toward arachidonate-containing DG and is shown to reside in the ER. Arachidonic acid, a precursor of bioactive eicosanoids, is usually acylated at the sn-2 position of phospholipids, being especially enriched in phosphoinositide. In this review, we focus on arachidonoyl-specific DGKε with respect to the historical context, molecular basis of the substrate specificity and ER-targeting, and functional implications in the ER.